Resilience intervention to Strengthen Self-Regulation in adolescent students with hearing loss - Adibsereshki, Narges; Hatamizadeh, Nikta; Kazemnejad, Anoshirvan; Sajedi, Firoozeh (European Journal of Mental Health, 2021)
Background: The importance of strong self-regulation (SR) abilities for academic and social success is known, yet relatively few studies examine students’ SR and how it can be promoted especially in adolescents with special needs, such as those students with hearing loss. The purpose of this study was to determine whether a resilience intervention program enhances SR in adolescents with hearing loss. Methods: This study was experimental with a pre-test, post-test, follow up and control group design. Participants included 122 students with hearing loss in mainstream settings randomly assigned to intervention and control groups (61 students in each group). The interventional group had training for six weeks (two times per week for 75 min). The Adolescent Self-Regulatory Inventory was used to measure the self-regulation of students. Results: The results indicated a significant difference between the control and interventional groups in SR, short SR, and Long SR after the intervention, at both the 6-week and 14-week measurements (p < 0.001). Conclusion: This study’s findings indicate that implementing resilience intervention programs can promote the self-regulation skills in adolescent students with hearing loss.